Current Problems of Indigenous Minorities of the Russian Arctic in the Context of Climate Change - Irina I. Matvienko (Арктика и Север, 2023)
The article describes the current problems of small indigenous peoples of the Russian Arctic in the context of climate change, the main of which are: the food problem, the problem of transport accessi-bility, the problem of economic activity and the problem of health. Because of global warming due to the increase in the average annual temperature, there is a high probability that the above-mentioned problems will only increase and significantly affect all life support systems of small indigenous peoples of the Russian Arctic. The article uses analysis and synthesis, induction and deduction to show the interconnection and mutual influence of the existing problems on the economic activity and health of small indigenous peoples in the conditions of climate change in the Arctic. In order to solve the current problems of the Russian Arctic indigenous minorities in the context of climate change, the following is required: 1) development of laws, strategies and/or state programs for the protection of indigenous peoples to minimize the adverse effects of climate change by sectors (reindeer herding, fishing, hunting and gathering); 2) creation of a system for assessing the impact of climate change on the economic activity and health of indigenous peoples; 3) participation of indigenous peoples in environmental monitoring and implementation of environmental projects in the Arctic.